Islam bicara soal seks, percintaan, dan rumah tangga / M. Sayyid Ahmad Musayyar ; editor Fathurrahman Yahya, Ahmad Tajudin - Musayyar, M. Sayyid Ahmad; Yahya, Fathurahman Tajudin, Ahmad (Erlangga, 2008)
XVI, 483 hlm. 19 cm.